Tomorrow's Arctic EIA: Nordic Possibilities and Perspectives to Environmental Impact Assessment in the Arctic Workshop Summary - SDWG (2017)
Nordic Workshop Summary: Tomorrow’s Arctic EIA – Nordic Possibilities and Perspectives to Environmental Impact Assessments in the Arctic, Rovaniemi, Finland 11–12 December 2017